T84. SLEEP QUALITY IN EARLY COURSE OF FIRST-EPISODE PSYCHOSIS. (9th April 2019) - Kohler, Christian; Villa, Prayosha; Schmidt, Lyndsay; Moore, Tyler; Calkins, Monica
Abstract: Background: Sleep disturbance is a common feature in early psychosis. Sleep quality has shown to be associated with both symptom severity and clinical improvement in persons with chronic illness. Understanding the influence of sleep quality in early psychosis can be beneficial in determining interventions for coordinated specialty care (CSC). Using patients from a CSC intervention program for first episode psychosis, we investigated the association between subjective sleep quality with clinical response and clinical symptom correlates. Methods: Participants were consecutive patients admitted between March 2015 to May 2018 who underwent coordinated specialty care at Penn PERC (Psychosis Evaluation and Recovery Center). Eligible participants were young persons ages 16–35 years who had experienced onset of psychosis within 2–3 years prior to intake and who underwent 2-years of CSC for early psychosis, including cognitive therapy for psychosis recovery (CT-R), medication management, family education and occupational support. Standardized self and observer-based rating scales evaluating sleep quality (PSQI) and other clinical symptoms, e.g., anxiety (BAI), depression (BDI), psychopathology (BPRS), affective states (PANAS), and clinical improvement (CGI-I) were administered at intake, after 3 months, 6 months and subsequently every 6 months of CSC. Participants provided informed consent. Correlational analysis were performed on PSQI change (slope) over 3 assessments and change in BAI, BDI, BPRS, PANAS-negative and -positive. Analysis were further stratified by improvement – CGI-I of 1 or 2 (much improvement) (n=31) versus CGI of 3 or greater (little/no improvement/worsening) (n=48). Results: In 87 patients, average age at intake being 22 years (Male:Female=68:19), overall PSQI ratings did not change significantly over time. BAI, BDI and BPRS scores significantly decreased over time, indicating overall clinical improvement with treatment. There was a trend for positive correlations among PSQI, and BAI, BDI and BPRS scores. When stratified by improvement, those rated as much improved experienced greater reduction of PSQI scores. Discussion: We found that subjective sleep quality did not change throughout course of treatment. However, improved sleep quality correlated with reduced subjective depression and anxiety symptoms and objective ratings. Though these findings do not address direction of causality, our findings indicate that improving sleep quality can be a specific focus in treatment of early psychosis. Further analysis will be conducted to investigate the relationship between sleep and other clinical and functional measures, and the dataset will be expanded to include data through the end of 2018.